Madrasah Principal Leadership Strategy to Build Teachers’ Teaching Spirit - Chandra, Chandra; Arumugham, Kalai Selvan (PPSDP International Journal of Education, 2025)
This study aims to identify the effective leadership strategies of madrasah principals in improving the teaching enthusiasm of teachers at Luqmanul Hakim Elementary Madrasah. The research method used is a case study with a qualitative approach. This study collects and analyzes various relevant literature sources, including journals, books, and scientific articles related to educational leadership and teacher motivation. The results of the study indicate that effective leadership strategies of madrasah principals in building teacher teaching enthusiasm include several key elements, namely open communication, professional development, and emotional support. The novelty of this study lies in the in-depth analysis of the psychological dimensions of teachers in responding to various leadership strategies. The contribution of this study is expected to provide recommendations for madrasah principals in designing more effective teacher development programs and become a reference for further research on teacher motivation in the context of Islamic education.